Effect of forging process on high cycle and very high cycle fatigue properties of TC4 titanium alloy under three‐point bending. Issue 8 (25th April 2021) - Wang, Bohan; Cheng, Li; Cui, Wenbin; Chen, Xuan; Wang, Changkai; Li, Dongchun
Abstract: The ultrasonic fatigue tests under two three‐point bending loading modes were carried out on TC4 specimens with the equiaxed, bimodal, and lamellar microstructure in the range of 10 5 to 10 9  cycles. The S ‐ N curves with different shapes were obtained, and it was found that the crack initiation in very high cycle regime changed from surface to subsurface. The crack initiation mechanism with different microstructures was revealed by fracture analysis. The axial tension influence mechanism is that it changes the axial stress distribution on the specimen cross section and makes the crack origin migrate to the interior.